Algoritmo genético aplicado ao controle do mosquito transmissor da dengue - Lyra, Luiz Gustavo [UNESP] (2014)
Dengue is a mosquito-borne viral infection found in tropical and sub-tropical regions around the world. In recent years, dengue disease has become a major international public health on concern. The World Health Organization (WHO) estimates that 50 100 million dengue infections occur each year and that over 2.5 billion people lives in more than 100 countries where dengue is endemic . Preventing or reducing dengue virus transmission depends on control of the mosquito vectors or interruption of human vector contact. In this work we studied a mathematical model that describes the populational dynamics of dengue's mosquito transmitter. This model describes the populational dynamics of mosquitoes in all stages of their development and discusses two methods to control mosquitoes, biological control with the release of sterile male mosquitoes in the environment and chemical control using insecticide. To evaluate these forms of control over the system is formulated a optimal control problem. Therefore, to assist in solving this problem we propose a genetic algorithm and the last we show computational results